DESKRIPSI WACANA HUMOR DALAM UPACARA ADAT PERNIKAHAN SEBAGAI WUJUD PELESTARIAN TRADISI LISAN DI MASYARAKAT - Lela Nurfarida; Diana Tustiantina (Jurnal Membaca Bahasa dan Sastra Indonesia, 2017)
In communicating, a strategy is needed to maintain the continuity of communication. One strategy that can be done to maintain communication is to reduce the risk of threatening the face of the speaker. In the event of humor, politeness is usually violated by speakers so that it potentially threatens the face of a person. Speech delivery strategy is concerned with how the speaker chooses to achieve the desired goal. The use of politeness as a balancing act of humor is one of the speakers' strategies for the purpose of maintaining the continuity of communication, as is done by the host in the marriage ceremony. In general, the expression of humor can be seen when the phrase has the potential to stimulate the opponent said smile or laugh. The phrase humor can be formed when any or all of the principles of cooperation (PKS) of Grice (1975) are violated. The offense was committed with the intention to convey the implied intent of mocking or insinuating causing humor. The method used in this research is descriptive qualitative. Sources of research data is a speech event of traditional wedding ceremony sunda. The research data is a cutting-edge utterance. In this study, the data is processed by step transcribing the source data research, analyze, and interpret data in the form of speech that contains humor. This research is expected to show the expression of humor can be done by violating the principle of cooperation Grice and speech defense that occurs in the wedding ceremony.